2015
DOI: 10.1080/07293682.2015.1047874
|View full text |Cite
|
Sign up to set email alerts
|

Age-friendly cities and communities: access to services for older people

Abstract: Australia's population is ageing rapidly, and our cities and communities need to be prepared to accommodate the needs of this increasing demographic to facilitate ageing in place. Ageing in place-where older people remain active and engaged members of the community-is influenced by access to services in the community. This paper introduces an indicator of access to services for older people that can be used to plan for age friendly cities. Development of the indicator was informed by qualitative research with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…These latter criteria being understood and relevant to most people, particularly older people, are particularly important and informed by previous research in the development of a specific indicator of access to services for older people [ 37 ], which included focus groups of older people to determine the local needs and services of highest importance. The selected measures also needed to be relevant to the majority of older people living in a wide range of lived environments, and to measure the most critical requirements for places that support AFC principles.…”
Section: Methodsmentioning
confidence: 99%
“…These latter criteria being understood and relevant to most people, particularly older people, are particularly important and informed by previous research in the development of a specific indicator of access to services for older people [ 37 ], which included focus groups of older people to determine the local needs and services of highest importance. The selected measures also needed to be relevant to the majority of older people living in a wide range of lived environments, and to measure the most critical requirements for places that support AFC principles.…”
Section: Methodsmentioning
confidence: 99%
“…In the study by other researchers, the importance of health and healthcare services was stressed and the importance of referring to family physician or pharmacies from the perspective of the old people was emphasized. In this regard, the findings of some researchers led to the inclusion of key services such as hospitals, family physicians, and care facilities for the old people in age-friendly city assessment indicators in Australia (Lowen et al 2015). In addition, a review article on age-friendly cities around the world found that provision of health and social services (with good quality) is considered a fundamental requirement in the development of societies and providing wellbeing for old people (Fitzgerald & Caro 2014).…”
Section: Coefficient Of the Modelmentioning
confidence: 99%
“…In this regard, countries with aging populations need to take the necessary precautions to meet this demographic change and provide favorable conditions for "ageing in place" (a situation which old people, in addition to being active and interacting with the community, have easy access to all services needed) (Lowen et al 2015). On the other hand, one of the main concerns of governments and policy makers in health sector, is the promotion of health in the community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional centralized living aging institutions, aging in place can provide Continuous, comprehensive aging services. Lowen, Davern, Mavoa and Brasher (2015) found the key point of aging in place, which should include health care, entertainment, public transports, home services, necessary facilities, etc [2]. In China, the effective supply of aging services in the elderly community is of shortage.…”
Section: Introductionmentioning
confidence: 99%